Preparation of BST Powders and Ceramics via a Hybrid Method - Thanawat Klaytae; Naratip Vittayakorn; Rattiphorn Sumang (Integrated ferroelectrics, 2023)
AbstractBarium strontium titanate (Ba0.8Sr0.2TiO3; BST) ceramics, were prepared by the hybrid method between Solid-state reaction (SSR) and Sol-gel methods (SG) in a ratio of 1:0.1–1:0.5. The BST powder was successfully calcined at 850 °C for 2 h. This temperature is much lower than the calcination temperatures of the SSR method. The BST ceramics were sintered between 1150 and 1450 °C. All samples showed the pure perovskite structure corresponding to JCPDS no. 34-0411. The optimum sintering temperature was observed from the samples sintered at 1450 °C for 4 h, indicating a density of 5.26 g/cm3, dielectric constant of 7018, and ferroelectric properties: (Pmax = 13.8 μC/cm2, Pr = 2.5 μC/cm2 and Ec = 2.3 kV/cm at 30 kV/cm).Keywords: Phase transitionmicrostructureferroelectrichybrid method AcknowledgmentsThe authors thank the Program of Physics, Faculty of Science and Technology, Pibulsongkram Rajabhat University for supporting facilities.Disclosure StatementNo potential conflict of interest was reported by the author(s).Additional informationFundingThis research was funded by Pibulsongkram Rajabhat University, grant number RDI-2-61-14. This work received the best poster award from the International Conference and Exhibition on Science, Technology and Engineering of Materials [ISTEM2022].
Keywords: Ferroelectric and Piezoelectric Materials; Dielectric properties of ceramics; Microwave Dielectric Ceramics Synthesis